Issues of the marketing mix’s formation and its relationship with competitive strategy’s development for educational services . - Kunanbayeva, D. A. (Journal of Economic Research & Business Administration, 2015)
There was considered number of options for marketing activities in situations when number of entrants is not as effective in ensuring sustainable development of the university. Marketing mix – is the combined use of a variety of marketing techniques. There are five main blocks in the marketing mix: a set of problems that determine the policy of the goods or services, prices, product distribution and communication, staff. Competitive strategy is based on the decisions that determine the set of tools, including tools update the range of services, pricing, communication, distribution and personnel and is specified in the plans of marketing activities, supported by an adequate budget, is embodied through the organization of marketing and subsequent management. Marketing in higher education seems to the author as a specific management system to determine the conditions that satisfy the consumers of educational services on the basis of marketing activities, taking into account the formation of the competitive strategy of the University, the propagation of information about the quality of educational services to consumers. Quality of educational services should be seen as an integral phenomenon, as polyfunction on several components. Was defined the role of marketing tools in the formation of the values of educational services. Marketing research is the starting point for the formation of the optimal strategy and tactics of thework of university. The paper describes the process of marketing research. According to the survey were identified marketing laws of formation of specialists in high demand